ANALISIS KEMAMPUAN CALON GURU MATEMATIKA DALAM MEMBUAT SOAL PEMECAHAN MASALAH MATEMATIKA - Umar, Ali; Lubis, Nur Ainun; Ahmad, Nurul Qomariyah; Saputra, Edy; Nasution, Mustafa Kamal (Universitas Islam Negeri Imam Bonjol Padang, 2021)
Problem solving is the main focus in learning mathematics at the primary and secondary school level. Prospective teachers must be prepared as well as possible as problem solvers and problem solving instructors. The purpose of this study was to describe the prospective teacher's ability to make a problem solving question based on category of good mathematical problem solving questions. The type of research used is descriptive qualitative.The research subjects were students of semester VI of the 2019/2020 academic year of the IAIN Takengon Mathematics Education Study Program. Based on the research results, it shows that the subjects in general already understood the theory of problem solving , but this understanding did not always directly proportional to the ability to make a mathematical problem solving question.